Drawing Ethical Principles from the Process of the Jerusalem Council: A New Approach to Acts 15:4-29 - Park, Hyung Dae (Tyndale bulletin, 2010)
This study proposes that the main ethical points found in the decision of the Jerusalem council in Acts 15:4-29 should include the council members’ attitudes of trusting each other, respecting God and his Word, and answering with some conceded responses to the others, rather than just the four prohibitions. To argue this proposal, first of all, the situation of the council is described in terms of the historical background and the narrative flow. The three lists of the four restrictions in 15:20, 29 and 21:25 are then compared, and the characteristics of the decision of the council are examined. The council’s list differs from James’ and has the perspective of worship and covenant rather than of ritual.